Control history, longitude and multiple abiotic and biotic variables predict the abundances of invasive brushtail possums in New Zealand forests - Forsyth, David M.; Ramsey, David S. L.; Perry, Mike; McKay, Meredith; Wright, Elaine F. (Biological invasions, 2018)
The factors affecting variation in the abundances of invasive mammal species have seldom been evaluated at large spatial scales. We used data collected in a large-scale biodiversity monitoring program to identify variables predicting abundances of common brushtail possums ( Trichosurus vulpecula ; ‘possum’), a marsupial folivore introduced to New Zealand in the 1800s. We sampled possum abundances, vegetation structure and composition, and abiotic variables at 395 spatially representative sites in natural forest on the North, South and Stewart islands. Records of possum control were obtained from management agencies. The large sample size enabled us to consider the relative importance of 27 variables for possum abundances. Twelve variables explained 80% of the contributions to the final boosted regression tree model. Control history had the largest contribution to the model, with sites subject to aerial 1080 poison baiting either once or more than once in the previous 7 years having possum abundances 64% and 74% lower, respectively, than sites without control. Possum abundances were also negatively related to humidity, stem density, tree cover density, slope, elevation and distance to pasture/crop. Abundances increased with increasing food plant species richness, Weinmannia racemosa (a preferred food tree) cover, and solar radiation. There was an interaction between longitude and control history. We conclude that invasive possum abundances in New Zealand’s natural forests are determined by multiple biotic and abiotic factors, sometimes in interaction. Recent control operations, however, have greatly reduced possum abundances. Increasing the spatial extent of aerial 1080 poison baiting will further reduce possum abundances in New Zealand forests.